O retalho pleural na perfuração do esôfago torácico - Andrade,Aderivaldo Coelho de (2010)
The thoracic esophageal perforations frequently complicate with fistula when submitted to primary suture. The use of autogenous tissues, like pleura, to reinforce the primary suture has proved to be useful in reduce the incidence of fistulas or at least the severity of the leaks in case they occur. The mortality has reduced too, consequently. A case of an extensive esophageal perforation is presented, where the use of pleural wrap to reinforce the esophagorrafy was very important to contain the leak and to permit a good evolution of the patient.